The in vivo metabolism of 3-oxo-5-benzylidene-6-methyl-(4H)-2-(benzoylmethyl)pyridazine in rats - (:unkn) unknown (MEDECINE ET HYGIENE, 2006)
The purpose of the study was to investigate the in vivo metabolic pathway of 3-oxo-5-benzylidene-6-methyl-(4H)-2-(benzoylmethyl)pyridazine (substrate) in rats. Firstly its potential metabolites, i.e. N-dealkylation, ling scission of pyridazine and aromatic hydroxylation products, were synthesized and then the substrate was given orally (100 mg/kg) to male or female Wistar rats at a dose of 100 mg/kg to body weight. Blood samples were collected at 0, 1, 2, 4, 6 and 8 hours after administration of substrate and blood was centrifuged to obtain serum. The substrate and its potential metabolites were separated using a gradient HPLC method on a reverse phase system. This study revealed that 3-oxo-5-benzylidene-6-methyl-(4H)-2-(benzoylmethyl)pyridazine was not metabolized to the proposed metabolites and was present unchanged in the serum.
Keywords: 3-oxopyridazine; in vivo metabolism; rat serum; EBASTINE